In Search of Shifting and Emergent Librarian Identities: A Philosophical Approach to the Librarian Identity Problem - Klein, Sara; Lenart, Bartlomiej (Partnership, 2020)
This paper argues that while the classical, essentialist conception of identity is appealing due to its simplicity, it does not adequately capture the complexity of professional or individual identity. The appeal to essentialism in librarianship contributes to some serious problems for the profession, such as exclusion and homogeneity in the workplace, high attrition rates of minority librarians, exploitation and alienation of an underrepresented workforce, as well as stereotyping. This paper examines the theoretical landscape with regard to the identity question and proposes a more fitting alternative to essentialism, namely the relational conception of identity, and engages in a philosophical argument for the adoption of the relational account as a theoretical grounding for an understanding of the complex, fluid, and emergent nature of librarian identity within our dynamic profession.